Civil-Military Relationship in a Democratic Pakistan - Muhammad Yunas Khan; Mubashar H. Jaffari (Policy Perspectives, 2023)
The paper explores the futuristic calibration of Pakistan’s constitutional development and its interpretation through precedents in the face of multiple sociopolitical, socioeconomic, and legal challenges. In particular, it analyzes the essential normative characteristics of constitutional legal framework based on separation of powers between pillars of the state vis-à-vis civil-military relationship. The article attempts to assess the constitutional direction from a broader legal and jurisprudential perspective meant to provide an avenue of progress and prosperity through its compatibility with sociopolitical norms. The main inquiry of the article is whether the constitutional evolution of Pakistan as a democratic state would be able to withstand the burden of contemporary socioeconomic, sociopolitical, and geopolitical challenges in creating a balance of power between civil and military institutions or would lead to more blurred boundaries instigating institutional conflicts and interventionist models. The paper through legal lens draws upon theories of legal positivism and its critique to understand the constitutional legitimacy of military interventions in democratic and political system. It covers the literature gap in analyzing jurisprudential approach of Pakistan’s judiciary as custodian of constitutional and democratic norms vis-à-vis constitutional scheme of civil-military relations, and its institutionalization in comparison with other international models suggesting pragmatic civilian control. In the end, the paper recommends a comprehensive institutional framework carved out of domestic realities as well as internationally-recognized constitutional schemes.